Macroprudential policy measures: Macroeconomic impact and interaction with monetary policy - Guido Cozzi; Matthieu Darracq Pariès; Peter Karadi; Jenny Körner; Christoffer Kok Sørensen; Falk Mazelis; Kalin Nikolov; Elena Rancoita; Alejandro Van der Ghote; Julien Weber (European Central Bank (ECB), 2020)
This paper examines the interactions of macroprudential and monetary policies. We find, using a range of macroeconomic models used at the European Central Bank, that in the long run, a 1% bank capital requirement increase has a small impact on GDP. In the short run, GDP declines by 0.15-0.35%. Under a stronger monetary policy reaction, the impact falls to 0.05-0.25%. The paper also examines how capital requirements and the conduct of macroprudential policy affect the monetary transmission mechanism. Higher bank leverage increases the economy's vulnerability to shocks but also monetary policy's ability to offset them. Macroprudential policy diminishes the frequency and severity of financial crises thus eliminating the need for extremely low interest rates. Counter-cyclical capital measures reduce the neutral real interest rate in normal times.
Keywords: E4; E43; E5; E52; G20; G21; 330; Monetary Policy; Bank Stability; Credit